Carcinoma breast presenting as a metastatic Kruckenberg tumor - S. G., Balamurugan; Fanny A., Giles; A. N., Lesin Kumar (International Surgery Journal, 2019)
Kruckenberg tumor is metastatic ovarian malignancy from primary gastrointestinal tract (GIT) or breast malignancy. Diffuse gastric carcinoma (linitis plastica) used to be the most common but lately there have been an increase in breast origin. It is usually found on carcinoma breast patients when we are evaluating for any metastasis. It is rare to find patients presenting with symptoms pertaining to metastasis, but not impossible. We are presenting such a rare case, where a patient presented with Kruckenberg tumor, which later was found to be a case of carcinoma breast. The prognosis of such patients are poor.